Filmic encounters: Multispecies care and sacrifice on island Timor. (7th January 2021) - Palmer, Lisa
Abstract: This is a story about the 'arts of noticing' more‐than‐human noticing. In it I reflect on the ways in which my own practice of ethnographic filmmaking is itself an agent of multisensory participation. As artifice and artificial eye, there is something both liberating and sensuous about filmmaking practice. It heightens the performativity of participants and their embodied rituals and allows me to enter intimate spaces I would otherwise not encounter. In these encounters a deep multispecies noticing takes place, although in the first instance this is usually only by the camera. The intimacy enabled in these artificial but sensorial encounters can be both revealing and confronting, especially in cases of animal sacrifice. Re‐encountering footage filmed across years of research‐led endeavour, in this paper I explore the power of film to convey these multisensory and multispecies stories, as well as to evoke understanding and engage the multisensory memory of the filmmaker.